Altered Lipid Composition of Secretory Cells Following Exposure to Zinc Can Be Correlated to Changes in Exocytosis. Issue 21 (13th March 2019) - Ren, Lin; Dowlatshahi Pour, Masoumeh; Malmberg, Per; Ewing, Andrew G.
Abstract: A micromolar concentration of zinc has been shown to significantly change the dynamics of exocytosis as well as the vesicle contents in a model cell line, providing direct evidence that zinc regulates neurotransmitter release. To provide insight into how zinc modulates these exocytotic processes, neurotransmitter release and vesicle content were compared with single cell amperometry and intracellular impact vesicle cytometry with a range of zinc concentrations. Additionally, time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) images of lipid distributions in the cell membrane after zinc treatment correlate to changes in exocytosis. By combining electrochemical techniques and mass spectrometry imaging, we proposed a mechanism by which zinc changes the fusion pore and the rate of neurotransmitter release by changing lipid distributions and results in the modulation of synaptic strength and plasticity. Abstract : Fat grafting with zinc : We have employed single‐cell amperometry and intracellular impact vesicle cytometry to measure the effects of zinc on exocytosis and vesicle content in PC12 cells. We also used mass spectrometry imaging to see the changes in lipid distribution of cell membrane after zinc treatment. Our results show that zinc alters lipid compositions, which can be correlated to the changes in exocytosis.